BUSINESS EDUCATORS' ASSESSMENT OF AVAILABLE ICT RESOURCES FOR TEACHING BUSINESS EDUCATION COURSES IN TERTIARY INSTITUTIONS IN SOUTH SOUTH NIGERIA. (NAU Journal of Technology and Vocational Education, 2024)
This study assessed available ICT resources for teaching business education coursesin tertiary institutions in South South Nigeria. One research question was raised andanswered while two null hypotheses were tested at 0.05 level of significance. The descriptivesurvey design was adopted for the study. The population comprised all 240 businesseducators in the colleges of education and universities in this area. The entire population wasused. A structured questionnaire was used as instrument for data collection. KunderRichardson statistics was used to establish the reliability; a reliability coefficient of 0.73 wasobtained. Data collected were analyzed using percentage, mean and standard deviation toanswer the research question and the null hypotheses were tested at 0.05 level of significanceusing t-test statistics. The findings showed there are no ICT resources for teaching businesseducation courses and that college of education have more ICT have more ICT resourcesthan the universities. Conclusions were drawn and relevant recommendations were madeamong others that government and relevant stake- holders should provide adequate andrelevant ICT resources for the teaching of business education courses in tertiary institutions.